(untitled) (Research, Society and Development, 2023)
The concern with the use of electricity is present nowadays, since natural resources are limited and human needs tend to be unlimited, whether due to population growth or the search for better standards of comfort, soon we can reach a point critical soon, due to the low in the hydroelectric reservoirs that are the biggest producers of our energy. Ecosystems are being degraded in the search for new energy sources to meet society’s needs. So that this does not happen, it is sought to reduce the use of natural resources, mitigating waste and increasing the efficiency of energy processes. This energy saving can be applied in various elements and ways, from energy generation to the consumer source. This work addresses the topic of Electric energy savings with sustainable applications in the face of a recession in electricity generation in the midst of a hydropower crisis in Brazil. The proposed objective is to show the need to create incentives for consumers to save electricity, in order to achieve a safe and sustainable use.